Crescimento inicial de pitaia (Hylocereus undatus) em função de combinações de doses de fósforo-zinco e nitrogênio-potássio - Almeida, Edmilson Igor Bernardo (2013)
The pitaya (Hylocereus undatus) is a cactaceous epiphytic, perennial succulent stem that presents the type cladodes, from where numerous adventitious roots which allows plant growth on trees and rocks in shaded environments of American rainforests. Although there was a great expansion of dragon fruit farm in Brazil and other countries of the world, the culture is still sorely lacking in studies and information that supports the definition/adaptation of production systems adapted to Brazilian soils and climate. To evaluate the effect of mineral fertilization on the early growth of pitaya and thus information directed to the definition of adequate fertilization managements of the farm culture, two experiments were conducted. Initially the initial growth of the plants was examined in the greenhouse for a period of 180 days, then to determine in the laboratory, the levels of nutrients in the soil, roots and shoots. We tested five doses of phosphorus (0, 75, 150, 255 and 300 mg dm-3) and zinc (0, 2, 4, 6 and 8 mg dm-3) in experiment I, and five doses of N (0, 150, 300, 450 and 600 mg dm-3) and K (0, 75, 150, 225 and 300 mg dm-3) in experiment II. Both experiments were arranged in a 5x5 factorial design with four blocks and 100 sampling units. At the end of this study it was found that the application of P and Zn, N and K, and interactions phosphorus-zinc and nitrogen-potassium affect the levels of the respective nutrients in the soil, roots and shoots, as well as the initial growth pitaya. The application of 150 – 225 mg dm-3 of P with 4 – 6 mg dm-3 Zn (experiment I), and 300 – 450 mg dm-3 of N with 150 – 225 mg dm-3 K (experiment II ) resulted in yields more satisfactory. This combinations of P and Zn, and N and K have provided 60 – 75 mg P dm-3 and 3.0 – 4.0 mg dm-3 of Zn in the soil; 4.5 to 6.0 g kg-1 P and 150 mg Zn kg-1 in shoots; 0.7 mmol dm-3 K in the soil; 20 – 25 g kg-1 of N and 30 – 40 g kg-1 K in shoots, respectively.